Legalized Adultery and Mental Health - Jiloha, R C (Journal of Advanced Research in Psychology & Psychotherapy (E-ISSN: 2581-5822), 2019)
Adultery is the sexual act between a married person and someone who is not that personâ€ºs spouse.1,2 The concept of adultery is embodied into the belief that the criminal intercourse with a married woman ... tends to adulterate the issue [children] of an innocent husband ... and exposes him to support and provide for another manâ€™s children3 and the â€œpurityâ€ of the children of a marriage is corrupted, and the inheritance is altered. Marital infidelity is not a socially acceptable behavior and extramarital sex is considered objectionable on various grounds such as religious, moral and ethical. Adultery invites condemnation and carries an implied judgment that the act is wrong.4 A single act of intercourse is sufficient to constitute adultery. Although the legal definition of adultery differs in nearly every legal system, the common theme is sexual relations outside of marriage, in one form or another.